2022
DOI: 10.3390/ijms23116199
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of N-Acetylcysteine with Cu2+: Appearance of Intermediates with High Free Radical Scavenging Activity: Implications for Anti-/Pro-Oxidant Properties of Thiols

Abstract: We studied the kinetics of the reaction of N-acetyl-l-cysteine (NAC or RSH) with cupric ions at an equimolar ratio of the reactants in aqueous acid solution (pH 1.4–2) using UV/Vis absorption and circular dichroism (CD) spectroscopies. Cu2+ showed a strong catalytic effect on the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) radical (ABTSr) consumption and autoxidation of NAC. Difference spectra revealed the formation of intermediates with absorption maxima at 233 and 302 nm (ε302/Cu > 8 × 103 M−1 cm−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 131 publications
1
5
0
Order By: Relevance
“…Unexpectedly, however, consistent with pro-oxidant effect of NAC in others studies [ 32 35 ], oral supplementation of NAC caused activation of inflammatory pathways and impaired the anti-inflammatory responses, as evidenced by the increase in TNF- α levels and decrease in IL-10, as well as macroscopic shortening of the colon. In contrast to the findings of the present study, Amrouche-Mekkioui and Djerdjouri [ 40 ] demonstrated that NAC decreased the production of inflammatory and LP markers (MPO and MDA).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Unexpectedly, however, consistent with pro-oxidant effect of NAC in others studies [ 32 35 ], oral supplementation of NAC caused activation of inflammatory pathways and impaired the anti-inflammatory responses, as evidenced by the increase in TNF- α levels and decrease in IL-10, as well as macroscopic shortening of the colon. In contrast to the findings of the present study, Amrouche-Mekkioui and Djerdjouri [ 40 ] demonstrated that NAC decreased the production of inflammatory and LP markers (MPO and MDA).…”
Section: Discussionsupporting
confidence: 86%
“…These results in liver and kidney, despite having been obtained in an animal model that mimics UC, shed light on the use of alternative therapies or not in individuals with IBD and who also present associated diseases, such as diabetes, liver, and kidney diseases, since NAC had shown to play a harmful role on markers that reflect metabolic and systemic integrity. This negative effect of NAC had been shown before in others studies [ 32 , 33 ] and can be explained by its pro-oxidant power, and, because of this property, has been tested to induce death in cancer cells [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, they suggested that GSH release by diatoms may contribute significantly to the Cu-binding ligand pool in marine waters [ 29 ]. Because of the biological and ecological importance of Cu–thiol complexes, Cu interactions with thiols have been of interest for many years, though there are discrepancies in the understanding of the exact reaction mechanisms and Cu oxidation state in such reactions [ 30 ]. Nevertheless, Smith et al reported that the stabilization of the free radical intermediate in Cu-catalyzed thiol oxidation varies as a result of structural differences between thiols affecting the oxidation rate, which is further discussed in their paper [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, CW can also be considered as a specific part of intermolecular chain transfers. However, its interest is due to the fact that it can lead to (hyper)branched/dendritic hydrocarbon polymers [24] that are tuned depending on the nature of the catalyst, [25,26,27,28,29] leading to stereospecific polymers, [28] or/with the complexity that the process involves the formation of radical species, [30] and this is also called radical ethene polymerization. [31,32,33] In addition, changing parameters such as monomer concentration or temperature can then block copolymerization.…”
Section: Introductionmentioning
confidence: 99%